2006
DOI: 10.1007/s10551-005-5496-z
|View full text |Cite
|
Sign up to set email alerts
|

Intra-organizational Volunteerism: Good Soldiers, Good Deeds and Good Politics

Abstract: Despite the millions of hours donated to charity each year by employees on behalf of their employers there has been relatively little research into the motives for such pro-social behavior. The current paper extends Peterson's (2004, Journal of Business Ethics 49, 371) study by exploring a unique form of employee volunteerism identified as intra-organizational, or employer-sanctioned volunteerism, and uniting the heretofore distinct charity support and organizational citizenship behavior literatures. Results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
217
1
20

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(246 citation statements)
references
References 56 publications
8
217
1
20
Order By: Relevance
“…Such interactions can lead to a high degree of relational embeddedness as individuals from both sides have more opportunities to develop attachments and personal relationships with one another. Thus, in the context of our study, we can expect a positive association between SA management routines and relational embeddedness, as literature indicates that the staff from both sides welcome such opportunities to develop such relationships if afforded the opportunity (Liu and Ko 2011b;Peloza and Hassay 2006;Peloza et al 2009). At the same time, we also need to acknowledge that the frequent interactions between SENPO and firm staff might breed resentment, as they are from discrete sectors with different organizational cultures, governance structures, and remunerative systems (Liston-Heyes and Liu 2013; Runté et al 2009;Samu and Wymer 2013).…”
Section: Mediating Role Of Relational Mechanismsmentioning
confidence: 78%
“…Such interactions can lead to a high degree of relational embeddedness as individuals from both sides have more opportunities to develop attachments and personal relationships with one another. Thus, in the context of our study, we can expect a positive association between SA management routines and relational embeddedness, as literature indicates that the staff from both sides welcome such opportunities to develop such relationships if afforded the opportunity (Liu and Ko 2011b;Peloza and Hassay 2006;Peloza et al 2009). At the same time, we also need to acknowledge that the frequent interactions between SENPO and firm staff might breed resentment, as they are from discrete sectors with different organizational cultures, governance structures, and remunerative systems (Liston-Heyes and Liu 2013; Runté et al 2009;Samu and Wymer 2013).…”
Section: Mediating Role Of Relational Mechanismsmentioning
confidence: 78%
“…These studies showed that people volunteer because of altruistic or egoistic motives, e.g., helping others or achieving goals (Cnaan and Goldberg-Glen 1991;Clary et al 1996;Thoits and Hewitt 2001;Peterson 2004;Burns et al 2006;Pajo and Lee 2011;Ferreira et al 2012;Do Paço et al 2013;Vázquez et al 2015). Further motives included personal dispositions, such as empathy or prosocial attitudes (Clary et al 1998;Davis et al 1999;Penner 2002;Hustinx and Lammertyn 2003;Peloza and Hassay 2006). One of the most comprehensive approaches to understanding motivation to volunteer was proposed by Clary and Snyder (1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Esta base teórica nos sirve para deducir que las instituciones no se crean por decreto, sino que son el resultado de un proceso de aprendizaje social; es decir, las organizaciones buscan legitimarse adhiriéndose a los valores deseados por las instituciones clave de la sociedad. En definitiva, la RSE -y más concretamente el VC-surge como una forma de legitimación social de la empresa (Peloza y Hassay, 2006;Basil et alii, 2009) debido a que el VC converge con la misión solidaria que la sociedad comienza a encomendar a las empresas.…”
Section: Marco Teóricounclassified
“…El trabajo en equipo (Peloza y Hassay, 2006), la comunicación, la gestión de proyectos y la generación de contactos con utilidad para el trabajo (Peterson, 2003), o la colaboración, son otras habilidades que se ejercitan con el VC. En realidad, casi todas las habilidades pueden ser desarrolladas con una gestión del VC orientada a este propósito, es decir, planificando, organizando, ejecutando y controlando los resultados del voluntariado aplicado (Tuffrey, 1998).…”
Section: Medición De Las Variablesunclassified
See 1 more Smart Citation